Pengaruh Financial Technology (Fintech) terhadap Kinerja UMKM di Kecamatan Alang-Alang Lebar dengan E-Commerce sebagai Variabel Moderasi - M. Zikrillah; Dewi Sartika (Masyarakat Ekonomi Syariah Bogor, 2025)
This research aims to analyze the influence of Financial Technology (Fintech) on the performance of MSMEs with E-Commerce as a Moderating Variable. This research uses quantitative methods by distributing questionnaires directly and via Google form to MSME owners. Based on the results of data analysis, it was concluded that there is an influence of Fintech on the performance of MSMEs in Alang-Alang Lebar District with a statistical T value of 15.772 at a significance level of 5%. And the P value of 0.000 which is smaller than 0.05 also supports the conclusion that Fintech has a significant effect on the performance of MSMEs. Apart from that, this research also tested the influence of Fintech on MSME performance with E-Commerce as a moderating variable which showed that it did not have a significant influence or weakened the relationship between Fintech and MSME performance with a statistical T value of 0.909 which was smaller than 1.96 and a P value of 0.363 which was greater than 0.05 indicating that the effect was not significant. This research provides an important contribution to understanding Financial Technology in increasing the efficiency and productivity of MSMEs.